Arte colaborativa como terreno de tecnodiversidade: DNA Afetivo Kamê e Kanhru e coletivo Jeapó - Mallmann, Kalinka Lorenci (2024)
The collaborative artistic practices developed with indigenous communities in Southern Brazil since 2016 are investigated, in this work, based on research in visual poetics. Between artistic works and theoretical reflections, a discourse is created that allows us to think about the concepts of cosmotechnics and technodiversity, both suggested by the Chinese philosopher Yuk Hui. These collective artistic productions, carried out with these communities, dialogue with their local demands and specificities, reinforcing the guidelines of contemporary collaborative art theorists, such as Grant’H Kester and Pablo Helguera. Both the DNA Afetivo Kamê and Kanhru project, in/with the Kaingáng community, and the practices of the Jeapó collective, in/with the Guarani Mbya community, allowed for cosmotechnical insights, which are revealed through a personal interpretative approach. This study problematizes how the scope of collaborative art can contribute to the realization of technodiversity in our contemporary society. Since technodiversity, in its multiple cosmotechnics, constitutes one of the possible paths to subvert the crisis we find ourselves in, based on a Eurocentric and hegemonic vision of the world and things in the world. Therefore, we can produce other technologies and not new technologies, diversifying the artistic and technological experience as alternative paths.